Detection of Toxocara sp. eggs in fecal samples from stray dogs in the Kembang Kuning Cemetery Area, Surabaya, Indonesia - Nugroho, Eko P.; Kurniabudhi , Marek Y. (Fakultas Peternakan Universitas Papua, 2026)
Dogs are common companion animals, and free-roaming dogs living in close proximity to humans may increase the risk of zoonotic disease transmission. One of the parasitic diseases of concern is toxocariasis, caused by nematodes of the genus Toxocara. Infection in animals may result in diarrhea, dehydration, anemia, and, in severe cases, death. This study aimed to detect the presence of Toxocara sp. eggs in fecal samples collected from stray dogs in the Kembang Kuning Cemetery area, Dukuh Kupang, Dukuh Pakis District, Surabaya. A total of 28 fecal samples were collected and initially examined using the native method. For each sample, 1 g of feces was mixed with 10 mL of distilled water, and 1–2 drops of the suspension were placed on a glass slide, covered with a coverslip, and examined microscopically. Twenty samples that were positive on native examination were subsequently tested using the flotation method. The fecal suspension was centrifuged at 3000 rpm for 10 min, repeated 2–3 times until the supernatant became clear. The sediment was then mixed with saturated sugar solution, covered with a coverslip, left for at least 20 min, and examined under a microscope at 400× magnification. The flotation test detected Toxocara sp. eggs in 17 of the 20 native-positive samples, equivalent to 85.0% of native-positive samples and 60.7% of all collected fecal samples. Three of the 17 Toxocara sp.-positive samples also contained Ancylostoma sp. eggs, indicating mixed infection. These findings demonstrate the presence of gastrointestinal helminth contamination in stray dog feces in the study area and highlight the potential zoonotic risk to the surrounding community.